INDONESIAN DEATH PENALTY: SEEN FROM THE CONCEPT BASED ON HUMAN RIGHTS - Muhammad Andy Hakim; Joko Setiyono (Diponegoro Law Review, 2020)
In the case of death penalty, Indonesia is a retentionist state of death penalty. It is evidenced through the regulation such as The Act Number 35 year 2009 on narcotics, The Act Number 1 year 1946 on criminal law regulation, The Act Number 31 year 1999 Jo The Act number 20 year 2001 about corruption and so on. Although Indonesia belongs to a retentionist country against death penalty, in the implementation remains in accordance with human rights. It was evidenced by ratifying international treaties relating to human rights and having legislation on human rights.